2017
DOI: 10.1093/schbul/sbx098
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Body Ownership in Schizophrenia: Experimental and Meta-analytical Approaches Show no Evidence for Deficits

Abstract: Schizophrenia is a severe psychiatric disorder, in which patients experience an abnormal sense of self. While deficits in sensorimotor self-representation (agency) are well documented in schizophrenia, less is known about other aspects of bodily self-representation (body ownership). Here, we tested a large cohort (N = 59) of chronic schizophrenia patients and matched controls (N = 30) on a well-established body illusion paradigm, the Full Body Illusion (FBI). In this paradigm, changes in body ownership are ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 88 publications
2
36
1
Order By: Relevance
“…However, it's not clear why they would show a drift further away from their location compared to when hearing someone else's voice. A previous study with a visually-driven experimentally-induced autocopy found no differences between schizophrenic patients and controls in neither self-location nor subjective responses (Shaqiri et al, 2018), while our study is yet to be tested with patients, these results might suggest changes compared to controls that are specific to self-related vocal-acoustic signals.…”
Section: Discussioncontrasting
confidence: 70%
“…However, it's not clear why they would show a drift further away from their location compared to when hearing someone else's voice. A previous study with a visually-driven experimentally-induced autocopy found no differences between schizophrenic patients and controls in neither self-location nor subjective responses (Shaqiri et al, 2018), while our study is yet to be tested with patients, these results might suggest changes compared to controls that are specific to self-related vocal-acoustic signals.…”
Section: Discussioncontrasting
confidence: 70%
“…Considered together, rubber hand illusion studies published to date thus support a diametric nature to rubber hand illusion susceptibility and strength in autism compared with psychotic-affective disorders. This hypothesis can be evaluated further by (i) including individuals on the autism spectrum, and the psychotic-affective spectrum, in the same rubber hand study, (ii) determining the degree to which the neurological and hormonal mechanisms of rubber hand effects also demonstrate diametric patterns, (iii) analysing in more detail the interpretation of verbal self-report, compared with proprioceptive drift based, measures of illusion presence and strength, and (iv) conducting studies of related bodily illusions, such as the full body illusion, in subjects with schizophrenia and autism; recent studies show that autism involves reduced effects of this illusion (as well as reduced peripersonal space) [121], though schizophrenia does not involve altered effects compared with controls [122]. Animal models should also be useful for additional tests, given the recent development of a ‘rubber tail illusion’ protocol in mice [123], for which autism-model knockout mice show reduced illusion effects compared with wild - types.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in somatoparaphrenia following focal brain damage, there may be a feeling that one's hand belongs to the self [5], [6] while damage to other brain regions may cause a loss of the sense of agency (but not hand ownership), as found in the so-called alien hand syndrome [7]- [9]. Similarly, in psychiatric conditions that cause alterations in the sense of self, there are conditions in which a dissociative experience of body ownership is a central symptom, as found in depersonalization [10], whereas schizophrenia patients experience a loss of agency [11]- [13] while body ownership is intact [14].…”
Section: Introductionmentioning
confidence: 99%